Genetic and phenotypic determinants of blood pressure and other cardiovascular risk factors (Swiss Medical Weekly, 2012)
BACKGROUND:The pathogenesis of elevated blood pressure and other cardiovascular risk factors in the population and their progression over time is still incompletely understood, especially in young and healthy adults. METHODS:The genetic and phenotypic determinants of blood pressure and other cardiovascular risk factors (GAPP) study is a population-based prospective cohort study involving a representative sample of healthy adults aged 25–41 years in the Principality of Liechtenstein. Exclusion criteria are any cardiovascular disease, diabetes, obstructive sleep apnoea syndrome, daily intake of nonsteroidal anti-inflammatory drugs and a body mass index >35 kg/m². Examinations include detailed assessment of personal, medical, lifestyle and nutritional factors, standardised assessment of weight, height and waist circumference, blood pressure measurement (clinic and 24-hour ambulatory monitoring), electrocardiography (12-lead and 24-hour Holter monitoring), bioimpedance analysis, blood, urinary and genetic sampling, spirometry and sleep pulse oximetry with nasal flow measurement. Baseline examination is still ongoing. Follow-up examinations are scheduled every 3–5 years. RESULTS:Since June 2010, 1,333 participants have been enrolled. Mean age of the participants was 36.7 ± 4.9 years and 47.5% of all participants were male. Mean body mass index was 26.1 ± 3.1 kg/m2 in men and 23.5 ± 3.9 kg/m2 in women. The prevalence of hypertension and prediabetes was 24.7% and 32.1% in men and 6% and 23% in women respectively. Mean LDL levels were 3.34 ± 0.9 mmol/l in men and 2.75 ± 0.7 mmol/l in women. Median hsCRP was 0.9 (0.5; 1.8) mg/l with no gender differences. CONCLUSION:GAPP affords an excellent opportunity to assess genetic and phenotypic predictors of cardiovascular risk factors and their progression over time in young and healthy adults from the general population.